Fundamentals of Machine Theory and Mechanisms - Simón Mata, Antonio; Bataller Torras, Alex.; Cabrera Carrillo, Juan Antonio; Ezquerro Juanco, Francisco; Guerra Fernández, Antonio Jesús; Nadal Martínez, Fernando; Ortiz Fernández, Antonio; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book covers the basic contents for an introductory course in Mechanism and Machine Theory. The topics dealt with are: kinematic and dynamic analysis of machines, introduction to vibratory behaviour, rotor and piston balance, kinematics of gears, ordinary and planetary gear trains and synthesis of planar mechanisms. A new approach to dimensional synthesis of mechanisms based on turning functions has been added for closed and open path generation using an optimization method based on evolutionary algorithms. The text, developed by a group of experts in kinematics and dynamics of mechanisms at the University of Málaga, Spain, is clear and is supported by more than 350 images. More than 60 outlined and explained problems have been included to clarify the theoretical concepts. .
Chapter 1 Kinematic Chains -- 1.1 Basic Concepts -- 1.2 Definitions -- 1.3 Degrees of Freedom of Mechanisms -- 1.4 Kinematic Inversions -- 1.5 Grashof's Criterion -- 1.6 Mechanical Advantage -- 1.7 Kinematic Curves -- 1.8 Application of Different Mechanisms with Different Purposes -- Chapter 2 Kinematic Analysis of Mechanisms. Relative Velocity and Acceleration. Instant Centers of Rotation -- 2.1 Velocity in Mechanisms -- 2.2 Accelerations in Mechanisms -- 2.3 Exercises with their Solutions -- Chapter 3 Analytical methods for the Kinematic Analysis of Planar Linkages. Raven's Method -- 3.1 Analytical Methods -- 3.2 Examples with their Solutions -- Chapter 4 Graphical and Analytical Methods for Dynamic Analysis of Planar Linkages -- 4.1 Machine Statics -- 4.2 Dynamic Analysis -- 4.3 Dynamic Analysis. Matrix Method -- 4.4 Exercises with Solutions -- Chapter 5 Balancing of Machinery -- 5.1 Rotor Balancing -- 5.2 Inertia Balancing of Single and Multi-Cylinder Engines -- 5.3 Problems with Solutions -- Chapter 6 Flywheel Calculations -- 6.1 Forces and Torques in Mechanisms -- 6.2 General Equation of Mechanism Motion -- 6.3 Working Periods of a Cyclic Machine -- 6.4 Steady State -- 6.5 Flywheels -- 6.6 Application Examples of Flywheels -- 6.7 Coefficient of Speed Fluctuation -- 6.8 Design of a Flywheel -- Chapter 7 Vibrations in Systems with one Degree of Freedom -- 7.1 Introduction to Oscillatory Motion -- 7.2 Single Degree of Freedom (SDOF) Systems -- 7.3 Free Vibrations in SDOF Systems -- 7.4 Forced Vibrations in SDOF Systems -- Chapter 8 Gears -- 8.1 Introduction -- 8.2 Toothed Wheels (Gears) -- 8.3 Condition for Constant Velocity Ratio. Fundamental Law of Gearing -- 8.4 Involute Teeth -- 8.5 Definitions and Nomenclature -- 8.6 Involute Tooth Action -- 8.7 Contact Ratio -- 8.8 Relationship between Velocity Ratio and Base Circles -- 8.9 Interference in Involute Gears -- 8.10 Gear Classification -- 8.11 Manufacturing of Toothed Wheels -- 8.12 Gear Standardization -- 8.13 Helical Gears -- 8.14 Bevel Gears -- 8.15Force Analysis in Toothed Wheels -- Chapter 9 Gear Trains -- 9.1 Classification of Gear Trains -- 9.2 Ordinary Trains -- 9.3 Planetary or Epicyclic Trains -- 9.4 Examples -- Chapter 10 Synthesis of Planar Mechanisms -- 10.1 Types of Synthesis -- 10.2 Function Generation Synthesis -- 10.3 Trajectory Generation Synthesis -- 10.4 Optimal Synthesis of Mechanisms -- 10.5 Analysis of the Objective Function -- 10.6 Optimization Method Based on Evolutionary Algorithms -- 10.7 Results -- Appendix I: Position Kinematic Analysis. Trigonometric Method -- I.1 Position Analysis of a Four-Bar Mechanism -- I.2 Position Analysis of a Crank-Shaft Mechanism -- I.3 Position Analysis of a Slider Mechanism -- I.4 Two Generic Bars of a Mechanism -- Appendix II: Freudenstein's Method to Solve the Position Equations in a Four-Bar Mechanism -- II.1 Position Analysis of a Four-Bar Mechanism by using Raven's Method -- II.2 Freudenstein's Method -- Appendix III: Kinematic and Dynamic Analysis of a Mechanism -- III.1 Kinematic Chain -- III.2 Slider Displacement versus Crank Rotation -- III.4 Velocity Analysis by Relative Velocity Method -- III.4. Instantaneous Center Method for Velocities -- III.5 Acceleration Analysis with the Relative Acceleration Method -- III.6 Raven's Method -- III.7 Mass, Inertia Moments, Inertia Forces and Inertia Pairs -- III.8. Force Analysis. Graphical Method -- III.9 Dynamic Analysis. Matrix Method. .
Keywords: Mechanical engineering; Multibody systems; Vibration; Mechanics, Applied; Mechanics; Mechanical Engineering; Multibody Systems and Mechanical Vibrations; Classical Mechanics